Kinematic and Kinetic Characteristics of Repetitive Countermovement Jumps with Accentuated Eccentric Loading - Micah Gross; Jan Seiler; Bastien Grédy; Fabian Lüthy (Sports, 2022)
Two methods for challenging the musculoskeletal and nervous systems to better exploit the stretch-shortening cycle (SSC) mechanism during plyometric training are reactive strength exercises and accentuated eccentric loading (AEL). Combining repetitive, reactive jumping with AEL poses a novel approach, in which the effects of both methods may be combined to elicit a unique stimulus. This study compared kinematic, kinetic, and electromyographic variables between a control (CON1) and two AEL conditions (AEL2 and AEL3). Additionally, non-reactive and reactive jumps performed within these sets were compared. Participants performed two sets of six countermovement jumps (CMJ) under each loading condition. AEL3 had moderate to large positive effects (es) on peak and mean eccentric force (es = 1.1, 0.8, respectively; both p < 0.01), and eccentric loading rate (es = 0.8, p < 0.01), but no effect on concentric variables or muscle activation intensity. The effects of AEL2 were similar but smaller. With or without AEL, there were moderate to large positive effects associated with reactive CMJ (second jump in a set, compared to the first) on peak and mean eccentric velocity (es = 1.7, 0.8, respectively; both p < 0.01), peak and mean eccentric force (es = 1.3, 1.2, p < 0.01), eccentric loading rate (es = 1.3, p < 0.01) and muscle activity (es = 1.8–1.9, p < 0.01). Concentric variables did not differ. Thus, the flight phase and act of landing during reactive jumps elicited greater increases in eccentric forces, loading rates, and muscle activity than AEL. Nonetheless, kinetic variables were greatest when AEL was combined with reactive jumping. Considering the limitations or complexity associated with most AEL protocols, sets of repetitive (reactive) CMJ may be more pragmatic for augmenting eccentric kinetic variables and neuromuscular stimuli during training.